The area of the circle by definition is given by:
![f (r) = \pi * r ^ 2 ](https://tex.z-dn.net/?f=%20f%20%28r%29%20%3D%20%20%5Cpi%20%20%2A%20r%20%5E%202%0A)
For f (r) = 154:
![154 = \pi * r ^ 2 ](https://tex.z-dn.net/?f=%20154%20%3D%20%20%5Cpi%20%20%2A%20r%20%5E%202%0A)
Clearing r we have:
![r ^ 2 = 154 / 3.14 r = \sqrt{154/3.14} r = 7](https://tex.z-dn.net/?f=%20r%20%5E%202%20%3D%20154%20%2F%203.14%0A%0A%20r%20%3D%20%20%5Csqrt%7B154%2F3.14%7D%20%0A%0A%20r%20%3D%207)
For f (r) = 616:
![616 = \pi * r ^ 2](https://tex.z-dn.net/?f=%20616%20%3D%20%5Cpi%20%2A%20r%20%5E%202%20)
Clearing r we have:
Answer:
a reasonable domain for f (r) is:
7 <r <14
The answer is 15 trust me.
Answer:
(a) The slope of f(x) is greater than the slope of g(x)
(b) f(x) has a greater y intercept
Step-by-step explanation:
Given
![\begin{array}{cc}x & {f(x)} & -1&-9&0&-1&1&7 \ \end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bcc%7Dx%20%26%20%7Bf%28x%29%7D%20%26%20-1%26-9%260%26-1%261%267%20%5C%20%5Cend%7Barray%7D)
![g(x) = 3x - 2](https://tex.z-dn.net/?f=g%28x%29%20%3D%203x%20-%202)
Solving (a): Compare the slopes
The slope (m) of f(x) is calculated as;
![m = \frac{f(x_2) - f(x_1)}{x_2 - x_1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7Bf%28x_2%29%20-%20f%28x_1%29%7D%7Bx_2%20-%20x_1%7D)
This gives:
![m = \frac{f(0) - f(1)}{0 - 1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7Bf%280%29%20-%20f%281%29%7D%7B0%20-%201%7D)
![m = \frac{f(0) - f(1)}{- 1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7Bf%280%29%20-%20f%281%29%7D%7B-%201%7D)
Substitute values for f(0) and f(1)
![m = \frac{-1 - 7}{- 1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B-1%20-%207%7D%7B-%201%7D)
![m = \frac{-8}{- 1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B-8%7D%7B-%201%7D)
![m = 8](https://tex.z-dn.net/?f=m%20%3D%208)
The slope of g(x) can be gotten using the following comparison
![g(x) = mx + b](https://tex.z-dn.net/?f=g%28x%29%20%3D%20mx%20%2B%20b)
![m \to slope](https://tex.z-dn.net/?f=m%20%5Cto%20slope)
So:
![g(x) = 3x -2](https://tex.z-dn.net/?f=g%28x%29%20%3D%203x%20-2)
![m = 3](https://tex.z-dn.net/?f=m%20%3D%203)
![m_{f(x)} > m_{g(x)}](https://tex.z-dn.net/?f=m_%7Bf%28x%29%7D%20%3E%20m_%7Bg%28x%29%7D)
Solving (b): Compare the y intercept
y intercept is when ![x = 0](https://tex.z-dn.net/?f=x%20%3D%200)
From the table of f(x)
![f(0) = -1](https://tex.z-dn.net/?f=f%280%29%20%3D%20-1)
From the equation of g(x)
![g(x) = 3x -2](https://tex.z-dn.net/?f=g%28x%29%20%3D%203x%20-2)
![g(0) = 3*0-2](https://tex.z-dn.net/?f=g%280%29%20%3D%203%2A0-2)
![g(0) =-2](https://tex.z-dn.net/?f=g%280%29%20%3D-2)
<em></em>
<em></em>
This answer is most likely wrong, but this is what I had gotten.
Using the formula BxH divided by 2, I came up with an answer of 108.
Answer:
Answer is C.
Step-by-step explanation:
If this answer helped u, pls mark as brainliest. thx!!!